Increased morbidity associated with chronic infection by an epidemic Pseudomonas aeruginosa strain in CF patients. Issue 4 (26th March 2004) - Al-Aloul, M; Crawley, J; Winstanley, C; Hart, C A; Ledson, M J; Walshaw, M J
Abstract : Background: Chronic pulmonary infection with transmissible Pseudomonas aeruginosa strains in individuals with cystic fibrosis (CF) has been reported, raising issues of cross infection and patient segregation. The first such strain to be described (the Liverpool epidemic strain, LES) is now widespread in many UK CF centres. However, whether such infection carries a worse prognosis is unknown. To address this, the clinical course of a group of CF patients chronically infected by LES was compared with that in patients harbouring unique strains. Methods: Using P aeruginosa strain genotyping, two cohorts of CF patients attending the Liverpool CF service were identified who were LES positive or negative in 1998 and remained so until 2002. From these, two groups of 12 patients were matched in 1998 for age, spirometric parameters, and nutritional state and their clinical course was followed for 5 years. Patients chronically infected with Burkholderia cepacia were excluded. Results: Patients chronically infected with LES had a greater annual loss of lung function than those not chronically infected by LES (mean difference between groups −4.4% (95% CI −8.1 to −0.9; p<0.02)), and by 2002 their percentage predicted forced expiratory volume in 1 second (FEV1 ) was worse (mean 65.0% v 82.6%, p<0.03). Their nutritional state also deteriorated over the study period (mean difference between groups in body mass index −0.7 (95% CI −1.2 to −0.2; p<0.01)), such that by 2002 they were malnourished compared with LES negative patients (mean BMI 19.4 v 22.7, p<0.02). Conclusions: Chronic infection with the Liverpool epidemic P aeruginosa strain in CF patients confers a worse prognosis than infection with unique strains alone, confirming the need for patient segregation. Since this strain is common in many CF units, strain identification in all CF centres is essential. This can only be carried out using genomic typing methods.